Bond Strength of Corroded High Yield Steel Bars Embedded in Normal Strength Concrete. (August 2019) - Thomas, T; Mirasa, A K; Rizalman, N
Abstract: Experimental investigation on the relationships between corrosion of reinforcement and concrete for the bond strength in pullout test and flexural test has been conducted to established the maximum strength. The reinforcing bars used in this study were rusted for four, eight and twelve months, it is cleaned for the eight and twelve months before embedded in concrete cubes for pullout test and concrete beams for the flexural test. The first component for experimental to make reinforce bars exposed to weathers and the parameter included 20 N/mm 2 concrete compressive strength. The diameters of reinforcing bars 12 mm, 16 mm and 25 mm used for tensile test and pullout test. 8 mm, 12 mm, 16 mm and 25 mm for flexural test. Tensile test carried out according to ASTM A615 16 and MS146:2006. Pullout test conducted according to ACI and BS 1881 Part 207:1992. Flexural test performed according to ACI and BS 8110 Part 1:1985, BS 1881 Part 109:1983 and BS 1881 Part 118:1983. All specimen's workmanship for reinforcement carried out according to BS 8110 Part 1: 1985 and to support this thesis based on previous literature review.